2008
DOI: 10.1007/978-3-540-89894-8_16
|View full text |Cite
|
Sign up to set email alerts
|

Parsing XML Using Parallel Traversal of Streaming Trees

Abstract: Abstract. XML has been widely adopted across a wide spectrum of applications. Its parsing efficiency, however, remains a concern, and can be a bottleneck. With the current trend towards multicore CPUs, parallelization to improve performance is increasingly relevant. In many applications, the XML is streamed from the network, and thus the complete XML document is never in memory at any single moment in time. Parallel parsing of such a stream can be equated to parallel depth-first traversal of a streaming tree. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…A large array of research results have been reported, which often exploit the SIMD instruction set extension of CPUs, or multicore CPUs to speed up XML processing in software [9][13] [14] [16]. However, their results are often incomplete, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…A large array of research results have been reported, which often exploit the SIMD instruction set extension of CPUs, or multicore CPUs to speed up XML processing in software [9][13] [14] [16]. However, their results are often incomplete, e.g.…”
Section: Introductionmentioning
confidence: 99%